ANALISIS PENERAPAN PEMIDANAAN PERBUATAN BERLANJUT DALAM PUTUSAN HAKIM MAHKAMAH AGUNG NOMOR 217 K/Pid/2020 - Ronald Septian Mandiri (Fakultas Hukum Universitas Tarumanagara, 2021)
Every country determines its own legal system without being influenced by other countries, criminal law is “Ultimate Remedium” or last resort in resolving a case in court, criminal law aims to: to protect the public interest, in the book of the Act. Criminal law is known to be concurrent, especially continuing acts. Continuing action is between several actions standing alone so that they must be seen as actions continue. In this case, there is a case of criminal prosecution for continuing the decision of the Supreme Court Judge Number 217 K/Pid/2020. How analysis of the application of criminal prosecution continues in the judge’s decision Supreme Court Number 217 K/Pid/2020. The author examines the problem using normative legal research methods. Data from the research shows that the decision of the Supreme Court to punish the act continues to impose the law is not right. The judge’s decision in his decision considers what judges are supposed to do.